Determination of Optimum TBARS Conditions for Evaluation of Cow and Sheep Milk Oxidative Stability - Oancea, Alexandra-Gabriela; Untea, Arabela Elena; Dragomir, Catalin; Radu, Gabriel Lucian (Applied sciences, 2022)
Having a complex fatty acid profile, milk is the subject of several oxidation processes that are different to those in other food matrices. Considering this, is important to appreciate the degradation status of milk using rapid and simple methods to quantify the main degradation products. The aim of this study was to adapt a simple and rapid method for determination of milk oxidative stability and to quantify malondialdehyde, one of the lipid oxidation products. Four parameters (trichloroacetic acid concentration—TCA, antioxidant type, incubation time, and thiobarbituric acid—TBA concentration) were modified to establish the best experimental sequence. It was concluded that the relevant results were obtained by precipitating milk proteins using 20% TCA; incubating samples for 90 min with 0.8% TBA, without adding antioxidant; and registering absorbance at three different wavelengths (450, 495, and 532 nm). This method was successfully applied to cow and sheep milk samples and the absorbance values obtained provided information about degradation of fatty acids for both milk types. The Pearson correlation showed a positive relationship between the fatty acid profiles of milk samples and the absorbance values that characterized their oxidation pattern during storage.